Peran Ulama dalam Legislasi Modern Hukum Islam - Ghofur, Abdul; Sulistiyono, Sulistiyono (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2015)
Fiqh paradigm shift in modern legal system necessitates acceptance of Jurisprudence of the diversity and plurality of the multiperspective such as democracy, human rights, the constitution, guarantee basic rights, and the realities of modern social life. As a product of legislation, modern Islamic law will be loaded with the demands, orientation, interests and voices of various parties to solve the various problems that arise. This paper is going to examine how the role of the scholars of Islamic law in modern legislation. This is related to the change in the legal paradigm of classical Islamic law based on individual ijtihad be based national parliament legislation which necessitates relevance ruling political authorities / parliament as the embodiment of a new meaning ijtihad definitively.